2012
DOI: 10.1073/pnas.1214094109
|View full text |Cite
|
Sign up to set email alerts
|

siRNA silencing of estrogen receptor-α expression specifically in medial preoptic area neurons abolishes maternal care in female mice

Abstract: The medial preoptic area has been shown to be intricately involved in many behaviors, including locomotion, sexual behavior, maternal care, and aggression. The gene encoding estrogen receptor-α (ERα) protein is expressed in preoptic area neurons, and a very dense immunoreactive field of ERα is found in the preoptic region. ERα knockout animals show deficits in maternal care and sexual behavior and fail to exhibit increases in these behaviors in response to systemic estradiol treatment. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 59 publications
1
69
1
Order By: Relevance
“…Recently, this technique was used to silence estrogen receptoralpha (ERa) expression in the preoptic area of female mice, given the role of this brain region in maternal care and aggression. Suppression of ERa strongly inhibited maternal care, but had no effect on maternal aggression toward a male intruder (Ribeiro et al 2012). This study is a good example of how RNAi can be a higher resolution technique for studying aggressive behavior.…”
Section: Advanced Methods and Future Agendamentioning
confidence: 99%
“…Recently, this technique was used to silence estrogen receptoralpha (ERa) expression in the preoptic area of female mice, given the role of this brain region in maternal care and aggression. Suppression of ERa strongly inhibited maternal care, but had no effect on maternal aggression toward a male intruder (Ribeiro et al 2012). This study is a good example of how RNAi can be a higher resolution technique for studying aggressive behavior.…”
Section: Advanced Methods and Future Agendamentioning
confidence: 99%
“…Region-and cell-specific ER knockout mice were used previously to understand estrogen's role in reproduction and neuroprotection (Dupont et al, 2000;Spence et al, 2011), demonstrating the feasibility of such animal models. Another approach that has recently been employed to examine the role of ERa in sexual and aggressive behavior has been to knock down protein expression using virally encoded si-or sh-RNA interference (RNAi) constructs in a brain-specific manner (Ribeiro et al, 2012;Sano et al, 2013). Such approaches, when combined with cell-specific promoters, would potentially enable examination of ER function in both a site-and cell-specific manner.…”
Section: B Studies Using Rodent Modelsmentioning
confidence: 99%
“…Estrogen sensitivity is critical for maternal behavior and its action is predominantly mediated by the two nuclear estrogen receptor subtypes (ER-α and ER-β) and they are expressed in a sex-specific manner [25,28]. ER-α has been shown to be involved in female maternal care and regulating anxiety and fear [13,31]. In the present study, we observed down-regulation of ER-α in POA of estradiol administered female rat which indicates that E2 induces important irreversible changes in terms of compromised feminine behavior as well as maternal care and also establishes defeminization during the adult stage.…”
Section: (Bottom Panel) Western Blot Analysis For Er-α Er-β and Famentioning
confidence: 99%